Larvacidal Effect of Methanol Extract from Soursop Leaves Against 3rd Instar Larvae of Culex sp. Mortality - Ni Putu Maitri Vidya Cita Riesky; Syamsul Bahri; Lalu Japa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
The Culex genus is widely distributed in Indonesia. It is responsible for disrupting and interfering of human daily activities and also transmitting some diseases for human. Vector control strategies normally involve the use of synthetic larvacide however excessive use causes adverse effect on environmental quality and resistance to larvae. Thus, extract from soursop (Annona muricata L.) leaves may be an alternative sources of larval control agents. The present study reveals the larvicidal effect of methanol extract from soursop leaves against 3rd instar larvae of Culex sp. mortality. Experimental method with Completely Randomized Design (CRD) consisting of 6 treatments (0 ppm, 125 ppm, 250 ppm, 500 ppm, 1000 ppm and 2000 ppm) and 4 replications was carried out with Culex sp. 3rd instar larvae and the larval mortality was recorded after 48 hours since the exposure. Data were analyzed using one way ANOVA which was continued by Tukey HSD and followed by Probit analyze to determine LC50 and LC90. The results showed that the methanol extract of soursop leaves exhibited significant larvicidal activity with LC50 and LC90 values are 586,099 and 2119,645 ppm. The highest concentration increases the mortality rate of larvae. In conclusion, the soursop leaves methanol extract has a larvacide effect on the 3rd larvae of Culex sp.